A Preliminary Evaluation of The Use of Graphic Novels in Teaching Information Systems - Aitken, Ashley; Hatt, G. (Deakin University, 2012)
As a result of declining student numbers, and poor satisfaction ratings, an introductory information systems unit was completely redeveloped. A number of innovative initiatives were designed and implemented and the unit has seen a significant improvement in student satisfaction rates. This paper describes the development of a series of graphic novels as a strategy to both increase student engagement with the unit content and enhance the attainment of learning outcomes. It also discusses how the graphic novels were used in lectures, workshops, and competitions to increase student engagement (with varying degrees of success). Students have generally found the graphic novels to be a valuable learning resource. There is a paucity of studies on the impact of graphic novels as a teaching tool, particularly within the context of higher education, and this research is a contribution to this evident gap in the literature.